Evaluation of Phenotypic and Genetic Parameters Affecting Reproductive and Productive Traits in Two Quail Strains - Tawfeq, Zhala Salar; Lajan Salahaldin Ahmed (Zanco Journal of Pure and Applied Sciences, 2025)
The study investigated the influence of genetic strain, generation, and their interaction on reproductive and productive traits in Ukrainian and Jumbo quail breeds. Ukrainian quails showed significantly (P≤0.05) superior reproductive performance, with higher fertility (90.06 vs. 84.43%) hatchability of set eggs (86.59 vs. 81.22%) and hatching weight (9.45 vs. 8.53g) compared to Jumbo quails, while hatchability of fertile eggs was similar. The progeny generation (G2) exhibited relatively improved fertility (89.52 vs. 84.98%) and hatchability of set eggs (85.00 vs. 82.81%) compared to the parent generation (G1), although G1 showed higher hatchability of fertile eggs (97.44 vs. 94.97%). Ukrainian quails reached sexual maturity earlier (35.50 vs. 36.00 days) and attained higher body weight at first egg (278.34 vs. 236.99 g) first egg weight (10.41 vs. 9.79 g) and mean egg weight (12.36 vs. 11.40 g). Phenotypic correlations revealed negative associations between age at maturity and body weight (r = -0.326) or egg weight (r = -0.112), and a positive correlation between body weight and egg weight (r = 0.492). Heritability estimates were higher for productive traits (h² = 0.56–0.62) than for reproductive traits (h² = 0.15–0.22). Strong genetic correlations (r = 0.43–0.57) between body weight and egg weight were observed. These findings provide insights for improving quail productivity through selection.